Development of Handout on Biodiversity Material Based on Gastropod Diversity in The Mangrove Ecosystem of Kayu Ara Permai Village, Siak Regency - Tia Oktaria Simarmata; Fitra Suzanti; Suwondo Suwondo (Journal of Education and Learning Research, 2026)
This study aims to determine the diversity of gastropods in the mangrove ecosystem of Kayu Ara Permai Village, Siak Regency, and to develop a biodiversity handout. The background of this study is the limited availability of teaching materials and the lack of contextual learning in schools. To address this problem, a handout based on local environmental potential was developed to help students understand the concept of biodiversity in a concrete and meaningful way. This study used a quantitative descriptive method, while the handout development followed the ADDIE model, including analysis, design, development, implementation, and evaluation, but was limited to the development stage. Gastropod data were collected using line transect and plot methods at three observation stations. The results showed that the gastropod diversity index was categorized as moderate, with six species found in various mangrove conditions. These findings were then used as contextual material in the development of the handout. Validation results by material and media experts showed that the handout was categorized as very valid in terms of content, language, presentation, and graphics. This study contributes by integrating local ecological research into contextual teaching materials, enhancing the relevance of biodiversity learning and supporting more meaningful learning experiences.